A Phase 2, Randomized, Open-Label Study of Irosustat Versus Megestrol Acetate in Advanced Endometrial Cancer. Issue 2 (1st February 2017) - Pautier, Patricia; Vergote, Ignace; Joly, Florence; Melichar, Bohuslav; Kutarska, Elzbieta; Hall, Geoffrey; Lisyanskaya, Anna; Reed, Nicholas; Oaknin, Ana; Ostapenko, Valerijus; Zvirbule, Zanete; Chetaille, Eric; et al.
Abstract : Objective: Advanced/metastatic or recurrent endometrial cancer has a poor prognosis. Malignant endometrial tissue has high steroid sulphatase (STS) activity. The aim of this study was to evaluate STS as a therapeutic target in patients with endometrial cancer. Methods: This was a phase 2, multicenter, international, open-label, randomized (1:1), 2-arm study of the STS inhibitor oral irosustat 40 mg/d versus oral megestrol acetate 160 mg/d in women with advanced/metastatic or recurrent estrogen receptor–positive endometrial cancer. The primary end point was the proportion of patients without progression or death 6 months after start of treatment. Secondary end points included progression-free survival, time to progression, overall survival, and safety. Results: Seventy-one patients were treated (36 with irosustat, 35 with megestrol acetate). The study was prematurely stopped after futility analysis. Overall, 36.1% and 54.1% of patients receiving irosustat or megestrol acetate had not progressed or died at 6 months, respectively. There were no statistically significant differences between irosustat and megestrol acetate in response and overall survival rates. Irosustat patients had a median progression-free survival of 16 weeks (90% confidence interval, 9.0–31.4) versus 40 weeks (90% confidence interval, 16.3–64.0) in megestrol acetate patients. Treatment-related adverse events occurred in 20 (55.6%) and 13 (37.1%) patients receiving irosustat or megestrol, respectively. Most adverse events in both groups were grade 1 or 2. Conclusions: Although irosustat monotherapy did not attain a level of activity sufficient for further development in patients with advanced/recurrent endometrial cancer, this study confirms the activity of hormonal treatment (megestrol acetate) for this indication.